2018
DOI: 10.1016/j.aott.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Chondroblastoma: An evaluation of the recurrences and functional outcomes following treatment

Abstract: ObjectiveChondroblastoma is a benign aggressive tumor which needs surgical treatment and has a recurrence rate up to 35%. Extended (aggressive) curettage is the mainstay of treatment and local adjuvants have been reported to decrease the recurrence rate.MethodsThe recurrence rates and the functional results of 14 patients who were treated in our institution and 2 other patients who were treated elsewhere between the years 2004–2016 were evaluated. Seventeen cases (13 male, 3 female; mean age: 17.1 [range: 13 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 18 publications
1
40
1
Order By: Relevance
“…Surgical removal of the lesion and bone grafting in a large defect is the standard treatment for chondroblastoma [1,15]. For completely curettage of tumor and avoid recurrence, most authors advised adjuvant physical or chemical inactivation methods, including high-speed burr, electrocauterization, phenol, cryotherapy and ethanol [5,16]. High-speed burr, phenol and ethanol were more widely reported in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical removal of the lesion and bone grafting in a large defect is the standard treatment for chondroblastoma [1,15]. For completely curettage of tumor and avoid recurrence, most authors advised adjuvant physical or chemical inactivation methods, including high-speed burr, electrocauterization, phenol, cryotherapy and ethanol [5,16]. High-speed burr, phenol and ethanol were more widely reported in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The primary treatment for chondroblastoma is intralesional curettage with or without bone-grafting [4], and some authors preferred chemical or physical adjuvants inactivation to decrease tumor recurrence [5].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical removal of the lesion and bone grafting in a large defect is the standard treatment for chondroblastoma [1,2]. For completely curettage of tumor and avoid recurrence, most authors advised adjuvant physical or chemical inactivation methods, including high-speed burr, electrocauterization, phenol, cryotherapy and ethanol [5,18,19]. Ebeid WA et al [4] found a signi cantly lower recurrence rate in patients treated with thorough curettage and high-speed burr.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still no study on the comparison of these different adjuvant options and point out the optimal choice. Moreover, adjuvant therapies may cause an extensive tissue damage while killing tumor cells, and should be used carefully, especially for tumors involving the epiphyseal plate [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation